Effectiveness of Teacher Education Programs: A Descriptive Aggregation of Supervisor Ratings of Teachers Trained by The Renaissance Group (TRG) and the Teacher Education Council of State Colleges and Universities (TECSCU) Institutions - Tracz, Susan (Educational (Re)naissance, 2013)
This study aggregated supervisor’s ratings of teachers trained at The Renaissance Group (TRG) and the Teacher Education Council of State Colleges and Universities (TECSCU) institutions. Fourteen studies conducted by 12 universities or states were gathered, and 12 that met inclusion criteria were included in this analysis. The total number of survey items in all studies (N = 374) was coded into 13 variables. Frequencies of the percentages of ratings falling into below average, average, and above average for those variables were tabled. Supervisors consistently gave teachers very high ratings.